Anti‐PD‐1 antibodies in metastatic uveal melanoma: a treatment option?. (21st June 2017) - Bender, Carolin; Enk, Alexander; Gutzmer, Ralf; Hassel, Jessica C.
Abstract: Uveal melanomas (UMs) are a rare form of cancer with clinical and pathological characteristics distinct from cutaneous melanomas. Ipilimumab has shown efficacy and safety in the treatment of metastatic UM. This provides a rationale for treatment with other immune checkpoint inhibitors. This is a retrospective review of 15 patients with metastatic UM treated between June 2014 and February 2016, who received treatment with the anti‐PD‐1 Abs pembrolizumab or nivolumab. Patients were treated at two German university hospitals. Therapy was administered at the approved dosing schedules of 2 mg/kg q3w for pembrolizumab and 3 mg/kg q2w for nivolumab. Treatment was given until first tumor assessment and continued if tumor assessment showed disease control. Tumor assessments were performed at baseline and following scans every 12 weeks. Patients were monitored throughout for adverse events. Best response to treatment was stable disease in four patients. Eight out of 15 (53%) patients received treatment until first tumor assessment. As of February 2016, median progression‐free survival (PFS) is 3 months (range 0.75–6.75 months) and overall survival (OS) is 5 months (range 1–16 months). Eight out of 15 (53%) patients are still alive (two patients lost to follow‐up) with one out of four patients is in ongoing disease control. Patients with multiple organ metastases and elevated serum lactate dehydrogenase did not respond well to treatment. No objective response to PD‐1 Ab therapy was seen. Best response to treatment was stable disease in four patients. Treatment was well tolerated with manageable toxicity. Abstract : Response rates to PD‐1 Abs in patients with metastatic Uveal melanoma were low although we did see four patients benefitting from treatment. Patients with multiple organ metastases and elevated lactate dehydrogenase did not respond well to treatment.